Assessing the Attitude and Knowledge of Family Doctors in Sari Toward Monkeypox - Lotfollah Davoodi; Mohammad Khademlou; Bahareh Moayed Ahmadi; Masoumeh Abdi Talarpashti; Zohreh Alinasab; Sodabah Jafari; Mohammad Shahpoori; Somayeh Khakpour (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Monkeypox is a zoonotic disease, first identified in humans in 1970. Considering the importance of physicians' knowledge and attitude toward treating this disease, the current study was designed and implemented to determine the attitude and knowledge of family doctors in Sari, Iran, regarding monkeypox. Materials and methods: The present study is a descriptive and analytical study, with the statistical population comprising family doctors in Sari. Initially, a questionnaire containing questions evaluating the knowledge and attitude of family doctors was designed. Subsequently, data were collected through a census method. After data collection, the information was analyzed using SPSS version 16 and relevant statistical tests. Results: The participants in this study were 117 family doctors working in urban and rural areas. Descriptive data showed that 55% of the participants were male, while 45% were female. Additionally, 62% worked in urban areas, and 38% worked in rural areas. The average age of the participants was 47.10±8.07 years, and their average work experience was 17.30±5.17 years. The average knowledge score was 9.30±3.42, and the average attitude score was 3.5±1.70. Analytical data also indicated that the attitude score had a significant relationship with gender, while the knowledge score was significantly related to the place of work. Conclusion: The results of this study indicate that the knowledge and attitude of family physicians in Sari regarding monkeypox were at a satisfactory level. Therefore, automated information dissemination systems in the field of infectious diseases can effectively be utilized to spread information about important infectious diseases.